2016
DOI: 10.2215/cjn.13791215
|View full text |Cite
|
Sign up to set email alerts
|

The Players: Cells Involved in Glomerular Disease

Abstract: Glomerular diseases are common and important. They can arise from systemic inflammatory or metabolic diseases that affect the kidney. Alternately, they are caused primarily by local glomerular abnormalities, including genetic diseases. Both intrinsic glomerular cells and leukocytes are critical to the healthy glomerulus and to glomerular dysregulation in disease. Mesangial cells, endothelial cells, podocytes, and parietal epithelial cells within the glomerulus all play unique and specialized roles. Although a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 79 publications
0
65
0
3
Order By: Relevance
“…The TLR3/ IFN-β/MDA5/RIG-I/IL-6 axis may play a role in inflammatory reactions related to viral and ‘pseudoviral” infection in GECs, and IL-6 produced by such cells may induce immune and inflammatory reactions in other resident glomerular cells [11, 12]. Since GECs have been reported to interact with other intrinsic residual glomerular cells [1, 2, 11], initial regional neutrophil recruitment by GECs followed by TLR3 activation could trigger the development of GN, as is thought to occur in LN [5, 6, 8, 22]. Thus, identifying the specific mechanisms that underlie endothelial TLR3 signaling for the recruitment of circulating neutrophils via CXCL1, E-selectin, and IL-6 expression is desirable for the development of therapeutic strategies for GN [8, 22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TLR3/ IFN-β/MDA5/RIG-I/IL-6 axis may play a role in inflammatory reactions related to viral and ‘pseudoviral” infection in GECs, and IL-6 produced by such cells may induce immune and inflammatory reactions in other resident glomerular cells [11, 12]. Since GECs have been reported to interact with other intrinsic residual glomerular cells [1, 2, 11], initial regional neutrophil recruitment by GECs followed by TLR3 activation could trigger the development of GN, as is thought to occur in LN [5, 6, 8, 22]. Thus, identifying the specific mechanisms that underlie endothelial TLR3 signaling for the recruitment of circulating neutrophils via CXCL1, E-selectin, and IL-6 expression is desirable for the development of therapeutic strategies for GN [8, 22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to contributing to the formation of the blood vessels in glomeruli, which act as a glomerular filtration barrier, glomerular endothelial cells (GECs) have been shown to produce various functional molecules that regulate aspects of glomerular function, including blood coagulation, inflammation, and homeostasis [1, 2]. Dysregulated endosomal Toll-like receptor (TLR) signaling has been reported to result in sustained activation of the type I interferon (IFN) system, which may lead to the development of autoimmune diseases such as systemic lupus erythematosus [3].…”
Section: Introductionmentioning
confidence: 99%
“…Since GECs have also been reported to interact with intrinsic MCs, glomerular basement membrane and podocytes in the glomerulus [1, 2, 23], initial GEC injury followed by regional neutrophil recruitment could trigger the development of GN. Furthermore, the activation of TLR3 and downstream immune responses can be induced by both infectious pathogens and non-infectious stimuli such as endogenous ligands [13, 15], thus identifying that the specific mechanisms that underlie TLR3 signaling in GECs is desirable for developing therapeutic strategies for GN.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to any of these intrinsic cell types can therefore lead to the development of glomerulonephritis (GN) [1, 2]. It has also been reported that neutrophils, another circulating player, play a pivotal role in the initiation of GN [3].…”
Section: Introductionmentioning
confidence: 99%
“…While many renal pathologies are caused by leukocyte-mediated tissue injury (103,104), clinical and experimental data suggest a central role for platelets in a number of chronic and acute kidney disorders. In experimental mouse models and patients with different types of glomerulonephritis platelets accumulate in the kidneys and/or platelet-derived factors are systemically elevated (21,22,105–108).…”
Section: Platelet-leukocyte Interactions In Pathologic Conditionsmentioning
confidence: 99%